Al-Ṭarīqah al-Naqshabandīyah al-Khālidīyah fī Cianjur, Jawa al-Gharbīyah: Ta‘ālimuhā wa tuqūsuhā wa taṭawwurātuhā - Hasyim, Abdul Wahid (Studia Islamika, 2020)
This article explores the teachings, rituals and developments of the Naqshabandiyah Khalidiyah sufi order in Cianjur, West Java. It has been established since the mid-19th century and has played an important role in the spread of Islam in this area called the “Kota Santri/City of Islamic Students”. This is due to the followers of the sufi order still adhering to the principle of khalwat dar anjuman. This principle allows them to practice the spirituality of the sufi order without leaving their social roles and functions as citizens. It can be seen from the diversity of their backgrounds, who are not only farmers, traders and entrepreneurs but also government officials. Moreover, 15 percent of them are millennials. Through a historical approach, this article found that the Naqshabandiyah Khalidiyah sufi order in Cianjur has become an important part of the history of Islamic civilization in the West Java region. The teachings and rituals that blend with the surrounding community have illustrated the diversity of Islam in the archipelago which tends to be Sufi in style since the early days.